Gill and haematological alterations in Macrobrachium amazonicum adults in acute exposure to ammonia and nitrite isolated and combined. Issue 5 (24th September 2022) - Dutra, Fabrício Martins; Juvenal, Jonatan Raphael; Forneck, Sandra Carla; Brazão, Claudia Caramelo; Ballester, Eduardo Luis Cupertino
Abstract: The present study evaluated the isolated and combined effect of total ammonia and nitrite on Macrobrachium amazonicum adults through the median lethal concentration (LC50 96h), histological analysis of gills and total and differential haemolymph cell counts. Prawns ( n = 640; 9.8 ± 0.9 cm and 8.22 ± 1.29 g) were subjected to an entirely randomised design in a 4 × 4 factorial scheme. Individuals were exposed to total ammonia (0, 18, 36 and 72 mg/L) and nitrite (0, 1, 2 and 4 mg/L) alone and in combination. Interaction between the compounds was determined by summing the additivity of the substances ( S ) and by calculating the additivity index ( AI ). The LC50 96h of isolated compounds was 27.98 mg/L for total ammonia and 1.87 mg/L for nitrite. Total ammonia and nitrite combined showed an LC50 96h of 22.36 and 1.17 mg/L, respectively. The sum of additivity ranged from 2.70 to 1.42 and the AI indicated that the toxicity of the mixture was 1.70 to 0.42 times lower, indicating an antagonistic effect of the compounds. High total haemocyte counts (THC) were observed at the higher concentrations of both compounds at a shorter exposure time. Reduction in THC was observed in the treatments with a longer exposure time. Differential haemocyte counts were similar between treatments. Increases in the extent of regressive damage and organ index ( Iorg ) values occurred with increasing concentrations of isolated total ammonia and nitrite. Mild to moderate presence of progressive damage was observed at intermediate combined concentrations, which elevated the Iorg values. The interaction of total ammonia and nitrite promoted a reduction in mortality compared to treatment with the isolated compounds. Thus, the results obtained guide decision‐making in production systems, which are currently based on studies where the compounds were evaluated acting in isolation. Abstract : Total ammonia and nitrite combined generated antagonism. Less severe damage occurred on gills exposed to ammonia and nitrite. High THC are found in the highest concentrations of the nitrogen compounds.